Juvenile stem volume equations for planted Azadirachta excelsa in the state of Johore, Peninsular Malaysia - Ong, Kian Huat; Lim, Meng Tsai; Chubo, John Keen (Universiti Putra Malaysia Press, 2009)
Azadirachta excelsa or sentang is one of the important tree species grown in Malaysia. Equations for the predicting stem volume, from the ground to the tip for this species, are not available and hence this paper attempts to apply and examine the suitability of the existing volume equations for the species which can be used by plantation growers in Malaysia. Furthermore, the performances of available volume equations in Malaysia are seldom investigated. Evaluation is important to determine the usefulness and increase the confidence of using a model. Three commonly used models were compared using the data derived from 36 harvested trees to fit the equations. The addition of the weight function of 1/(d2h) was used to fit the Spurr’s combined variable volume equation. Then, the performances of the models were evaluated based on R2, PRESS, bias and RMSE values. The Schumacher and Hall’s equation was found to be the most appropriate for determining the total and merchantable underbark stem volume of A. excelsa, whereas the Spurr’s equation was indicated as more suitable to determine the merchantable overbark volume.